Gut microbiota modulation and health benefits of various fasting regimens - Sumel Ashique; Biplab Debnath; Naheed Mojgani; Mohd. Tariq; Tanweer Haider; Eman Shorog; Sabina Yasmin; Anas Islam; Himanshu Sharma; Md Sadique Hussain; Ayush Madan; Tabarak Malik; et al. (Current Research in Biotechnology)
Fasting is a diet intervention that has been shown to significantly modulate the gut microbiota, with potential health benefits. This review examines the impact of various fasting regimens, including time-restricted eating (TRE), Ramadan fasting (RF), and long-term fasting, on the composition and function of the gut microbiota in both animal models and human subjects. Studies have shown that fasting can increase microbial diversity, enrich beneficial bacteria such as Faecalibacterium prausnitzii, Roseburia spp., Akkermansia muciniphila, and other Lachnospiraceae, and enhance the production of short-chain fatty acids (SCFA) such as butyrate. These microbiota changes are associated with improvements in metabolic health markers, including body weight, blood pressure, glucose regulation, and lipid profiles, as well as reduced inflammation. However, the persistence of these effects after fasting varies between studies. Dietary changes during fasting, such as meal timing and composition, play a crucial role in shaping the response of the gut microbiota.Although most studies report beneficial results, heterogeneity in results highlights the need for more research to elucidate the relative contributions of factors such as age, baseline diet, habitual microbiota composition, fasting duration, and caloric content. The mechanistic links between specific microbial metabolites and clinical endpoints remain limited, and evidence for the synergistic effects of probiotics with fasting in humans is inconclusive. Future studies should employ standardized fasting protocols, integrate multi-omics approaches, and extend follow-up periods to determine the durability of microbiota and metabolic shifts. Developing personalized fasting strategies tailored to an individual’s baseline microbiota and metabolic phenotype may optimize the therapeutic potential of fasting for gut and metabolic health.